Estimation of gas induction in jet loop reactors: influence of nozzle designs - Sharma, D.V. (Chemical Engineering Research and Design, 2017)
Jet loop reactors are used widely for conducting gas liquid reactions because of the high mass transfer achieved in the gas–liquid ejector. Studies have shown that the mass transfer has a very strong correlation to the amount of gas induced in the ejector, and hence it is important to understand gas induction to enhance the performance of any gas–liquid nozzle. In this work, we used a single phase CFD model of the ejector with one adjustable parameter for estimating gas induction rates. After establishing that the model adequately describes the experimental data, the model was used for a quick evaluation of ejector geometries. Influence of key geometric parameters of gas–liquid ejectors like nozzle diameter, mixing tube length, distance between the nozzle outlet and mixing tube, suction chamber geometry and diffuser angle was investigated. It was found that dependence of gas induction on geometric parameters like distance between nozzle—mixing tube, suction chamber geometry, diffuser angle was either weak or had a clear maxima at or beyond a certain value of the geometric parameter. Other parameters like mixing tube length and nozzle diameter have a more complex impact on gas induction. The presented approach and results will be useful for quantifying influence of nozzle designs on gas induction rate in jet loop reactors.
Keywords: CFD; Gas Induction; Jet Loop Reactors; Nozzle Geometry